Clostridial gas gangrene involving the brain, gallbladder, heart, and soft tissue: A case report and literature review - Ashton D. Hall; Joshua M. Ferreri; Jennifer E. Baker; Eleanor A. Powell; Imran Ahmed; Timothy T. Klostermeier; Keith M. Luckett (IDCases)
Clostridial gas gangrene (CGG) is among the most rapidly spreading infections in humans, with mortality rates approaching 100 % if not treated promptly. Most cases follow traumatic inoculation, although spontaneous infections occur in a minority of patients with immunodeficiency. Spontaneous CGG is primarily caused by Clostridium septicum, whereas traumatic infection is associated with Clostridium perfringens. Patients with CGG present abruptly with rapidly progressive symptoms, underscoring the importance of early recognition, prompt surgical intervention, and appropriate antimicrobial therapy. We describe an illustrative case of spontaneous CGG caused by C. perfringens in a polymorbid 73-year-old female patient. Despite aggressive medical and surgical management, she succumbed to metastatic infection within 48 h of presentation.